Percepções gestores/as diante do programa escola sem partido: sua ideologia está a serviço do que e de quem? - PAIAS, Kátia Rodrigues Montalvão (2019)
This dissertation, linked to the Graduate Program in Education of the University of Oeste Paulista (Unoeste), the research line Public Policies in Education, Educational Practices and Diversity and the research group Estado, Educational Policies and Democracy (EPED), aimed to identify and analyze the reasons that lead school principals to support or refute the School Without Party Program, besides to investigate the theoretical conceptions that help these teachers in their interpretations of the Program. The research is based on the perspective of the Method of Historical-Dialectical Materialism. As methodological procedures were used the documentary analysis, especially of the Law n. 867 of 2015, as well as semi-structured interviews with the principals of state schools in a medium-sized city in northwestern Paraná. The data analysis took place in the announced perspective, in order to verify the contradictions present in the managers' discourses. The data revealed that, of the ten participants, nine refuted the School Without Party Program, alleged that it generates violence, which accentuates social inequality, which does not develop the critical sense of the students, which promotes a contentious education, which it hurts the right to chair, as well as censuring teachers. Only one director agreed with the Program, claiming that it would be better for teaching, as the teacher will focus on the transmission of content, should maintain neutrality and that the program avoids violence.